College Students Attributional Differences in Knowledge Awareness about a Cybercrimes Law - Al-Badayneh, Diab M.; Dosari, Hamad M. Al; Qahtani, Hamed M. Al; Alkhater, Jassem A.; Mehawesh, Sada S. (Journal of Ecohumanism, 2024)
The study examines attributional differences in assessing the level of knowledge awareness about Jordanian Cybercrimes Law (JCL) among college students. The study sample comprised 500 Jordanian students representing four Jordanian universities (TTU, MU, JU, & BU). Of these, 43% were males, and 57% were females. Students (19%) reported being victims of cybercrimes, and 24% were perpetrators. Reliability as estimated by the scale’s Cronbach’s α was 0.66, and the validity (correlation between the scale and LSC scale) was 0.157 α = 0.00 (F = 187.161, α = 0.00). More than 25% of the sample read about the JCL and observed that the law has been politicized. Moreover, three-quarters of them heard about it. More than half of the sample witnessed illegal actions on the net that required punishment. Less than 10% of the sample dealt with the JCL or participated in an online action that required punishment. ANOVA analysis of the mean gender differences in cybercrime knowledge showed females were more knowledgeable about JCL than males (F = 4.402, α =.036). Furthermore, an ANOVA analysis of the mean external attribution differences (yes vs. no) in JCL knowledge (F = 4.402, α =.036) was performed. Finally, ANOVA analysis of the mean external attribution differences in the knowledge of JCL (F = 4.402, α =.036).